Oil spills characterization and modeling using remote sensing and geophysical techniques to protect the highly vulnerable coastal zones in Alexandria, Egypt - Attwa, Mohamed; Elkafrawy, Sameh B.; El Bastawesy, Mohammed; Abd El-wahid, Kareem H.; Abotalib, Abotalib Z.; Talal, Ahmed; Shehata, Mohamed (Marine pollution bulletin, 2024)
Nowadays, oil spills threaten both aquatic and terrestrial environments, especially in regions with intensive oil refining and shipping activities and high environmental sensitivity, such as Alexandria city, Egypt. Oil spill characterization in coastal populous cities is particularly difficult due to large chemical/physical soil heterogeneities and saltwater intrusion, which represent a major challenges for soil remediation and restoration. Recently, the development of inversion algorithms enables electrical resistivity imaging (ERI) to perform detailed characterization of near-surface soil pollution. The study implements an interdisciplinary approach using remote sensing and an advanced time-lapse 2D-inversion scheme for detailed characterization of oil spill patterns around oil refinery sites in the Alexandria coastal zone. The implemented scheme was able to improve the depth of investigation while maintaining the shallow lateral model resolution. The findings indicate that the mapped oil spills constitute a wedge-like form where the oil moves gradually downward, and it then shifts horizontally towards the shoreline with thinning in oil-contaminated zones under control of tidal action and ground surface slope. Consequently, guided by remote sensing observations, in-situ trenches/wells are suggested to withdraw the oil-contaminated water at the maximum deduced oil-contaminated soil thickness. The applied procedures in this study are replicable and can be effectively used as a pre-requisite to remedy oil spills along terrestrial coastal environments worldwide. A Simulation model for a better understanding of the oil spillage representing the proposed remediation action along the coastal zone. [Display omitted] •An interdisciplinary approach of RS and time-lapse 2D-ERI data is adapted.•An advanced inversion scheme is used to characterize the oil-contaminated soil.•Planet and Google Earth images are utilized for visual interpretation and validation.•Oil spills along vulnerable coastline margins are characterized and understood.•A proper remediation action of the soil pollution is suggested.